The Narrative Power of Things - Vilain, Robert,Schofield, Benedict,Lloyd, Alexandra,Wismeg-Kammerlander, Rebecca (Peter Lang Ltd. International Academic Publishers, 2023)
This book unveils how a skilful reading of consumer objects can enrich literary analysis. Focusing on Austrian writers Haas, Glavinic, Geiger and Edelbauer, the study showcases the narrative power of consumer goods and the impact of Austrian literature and its writers on the idyllic national brand that stands in stark contrast to a troubled past.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Haas; Wolf; Glavinic; Thomas; Geiger; Arno; Edelbauer; Raphaela; Das Wetter vor 15 Jahren; Die Arbeit der Nacht; Es geht uns gut; Das flüssige Land; Konsumgut; Verbrauch